2008
DOI: 10.1095/biolreprod.107.066662
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Epigenetic Modifications of Donor Somatic Cells on the Subsequent Chromatin Remodeling of Cloned Bovine Embryos1

Abstract: Evidence indicates that failure of nuclear transfer (NT) embryos to develop normally can be attributed, at least partially, to the use of differentiated cells as the donor karyoplast. Blastocyst production and development to term of cloned embryos has been hypothesized to differ between population doublings of the same cell line as a consequence of changes in the levels of DNA methyltransferase 1 (DNMT1) and methylated DNA during in vitro culture. The objective of this study was to determine embryo production,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…In addition, our results demonstrate that a temporal reduction in DNMT1 mRNA levels during the early stages significantly improved the in vitro development of bovine NT embryos (Table 2). Our finding that a reduction in DNMT1 mRNA improved early developmental competence is consistent with work by Giraldo et al [25] that also showed an improvement in early developmental competence in a donor cell line with low levels of DNMT1. Similarly, Wee et al [11] reported that treatment of donor cells with Trichostatin A, an inhibitor of histone deacetylase, prior to NT decreased levels of DNA methylation in the satellite I region and improved early developmental competence of bovine NT embryos.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, our results demonstrate that a temporal reduction in DNMT1 mRNA levels during the early stages significantly improved the in vitro development of bovine NT embryos (Table 2). Our finding that a reduction in DNMT1 mRNA improved early developmental competence is consistent with work by Giraldo et al [25] that also showed an improvement in early developmental competence in a donor cell line with low levels of DNMT1. Similarly, Wee et al [11] reported that treatment of donor cells with Trichostatin A, an inhibitor of histone deacetylase, prior to NT decreased levels of DNA methylation in the satellite I region and improved early developmental competence of bovine NT embryos.…”
Section: Discussionsupporting
confidence: 92%
“…Giraldo et al. [25] demonstrated that NT embryos obtained using donor cells with low expression of DNMT1 mRNA were associated with a higher developmental competence compared with NT embryos obtained using donor cells with high expression of DNMT1 mRNA. Based on these findings, we hypothesized that a method for reducing the levels of DNMT1 mRNA during the first embryonic divisions would prevent the hypermethylation of genomic DNA.…”
mentioning
confidence: 99%
“…Culture conditions of embryos, particularly the presence of serum in culture medium, could affect expression of this gene, as observed previously by Fernández-Gonzalez et al (2009) in mouse andPandey et al (2010) in buffalo SCNT. Giraldo et al (2008) reported that abnormal pattern of transcript may be due to epigenetic modifications due to culture conditions, which directly affect chromatin remodelling and is correlated to imprinted genes. Differences were found in our study for embryos cultured in the presence and absence of serum, may suggest that other factors such as culture medium composition could be responsible for alterations of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Because a hypermethylation status of the genome has consistently been observed in bovine SCNT embryos [20][21][22][23], decreasing the levels of DNA methylation in donor cells prior to nuclear transfer might improve developmental competence of SCNT embryos. Therefore, DNA demethylation by siRNA might be a strong tool for analyzing the reprogramming mechanism, resulting in improvement of cloning efficiency.Giraldo et al [45] recently reported that the developmental competence of SCNT embryos obtained using donor cells with a low expression level of DNMT1 mRNA is higher than that of SCNT embryos obtained using donor cells with a high expression level of DNMT1 mRNA. Likewise, it has been reported that global hypomethylation of the genome in mouse fibroblast cells carrying a hypomorphic allele of the DNMT1 gene improves the efficiency of generation of embryonic stem cells from SCNT blastocysts [46].…”
mentioning
confidence: 99%